From Ancient Traditions to Modern Design: Interpretation of Some Ornaments on Leathercraft Items - Khayrullina-Valieva, Albina (Lietuvos istorijos studijos, 2023)
Information about the art and design of Tatar footwear, revealed in different historical records, travel diaries, and descriptions of museum collec- tions, is of great importance. It allows us to assume a strong traditionalism of leather mosaic in the Tatar folk decorative and applied arts. This assumption is also supported by the stylistic uniformity of a large number of decorative mo- tifs, the similarity of principles in composition and colour solutions identified with the comparative analysis of leather mosaic and other traditional types of national applied art. The development of style and technical methods of leath- er mosaic can be assessed by retrospective comparison with later monuments. Wise selection of innovations has always been a wizard of classical folk art. Folk craftsmen had an amazing intuition and only features suitable for adaptation and standardisation were included in the traditional art set. Due to the histor- ical succession, the art of leather mosaic stepped over the centuries, perfecting and improving its distinctive features.